Extended-spectrum β-lactamase-producing Enterobacterales among people living with human immunodeficiency virus across the globe: A systematic review and meta-analysis - Mitkie Tigabie; Abebe Birhanu; Muluneh Assefa; Getu Girmay; Kebebe Tadesse (PLoS ONE, 2025)
Background People living with HIV are vulnerable to antibiotic-resistant bacterial infections because of frequent healthcare visits, the consumption of many antimicrobials, and the weakened immune system to fight infections. Our objective was to provide comprehensive data about ESBL-producing Enterobacterales among HIV-positive individuals across the globe. Methods This meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. To select eligible articles published between January 1, 2010, and May 12, 2024, a literature search was performed on available electronic databases such as PubMed, Hinari, Google Scholar, and Scopus. The quality of the included studies was assessed via the Joanna Briggs Institute critical appraisal tool. The data were extracted from the eligible studies via Microsoft Excel 2019 and analyzed via STATA version 17. A random effects model was constructed via the DerSimonian and Laird method. The heterogeneity was checked through the Cochrane Q statistic, and the magnitude was quantitatively measured via I2 statistics. To determine the possible sources of heterogeneity, a subgroup analysis was performed. Additionally, a sensitivity analysis was conducted, and publication bias was checked via funnel plots and Egger’s regression tests. A p value of less than 0.05 was considered evidence of heterogeneity and small study effects according to the Cochrane Q statistic and Egger’s test, respectively. The protocol was registered previously (PROSPERO ID: CRD42024557981). Results A total of 5305 HIV-positive individuals from 20 studies were included in our meta-analysis. The overall pooled prevalence of ESBL-producing Enterobacterales among HIV-positive individuals was 20.30% (931/5305; 95% CI: 15.13–25.47%, P < 0.001), with a high level of heterogeneity (I2 = 97.82%, P < 0.001). The predominant ESBL producers were K. pneumoniae, with a pooled prevalence of 40.84% (76/217; 95% CI: 26.87–54.81%), followed closely by E. coli at 40.14% (348/985; 95% CI: 27.83–52.45%). In the subgroup analysis, the highest magnitude of ESBL-producing pathogens was observed in Asia (195/715; 28.55%), followed by Africa (666/3981; 19.12%). Additionally, the highest pooled prevalence of ESBL-producing pathogens among HIV-positive individuals was reported to be colonization 23.78% (613/2455; 95% CI: 15.36–32.19, I² = 96.78%, p < 0.001), followed by infection 15.77% (318/2850; 95% CI: 10.06–21.49, I² = 97.45%, p < 0.001). Among the different types of ESBL enzyme-encoding genes, blaCTX-M was the most common (73 out of 150 isolates, 48.7%), followed by blaTEM (49 out of 150, 32.7%). Conclusion and recommendations This study demonstrated that HIV-positive individuals are commonly colonized and infected with ESBL-producing Enterobacterales. The highest prevalence of these pathogens was reported in Asia and Africa. To reduce mortality from severe bacterial infections in HIV patients, resources should be distributed equitably across all regions. Particular attention should be given to high-prevalence areas, where early detection of colonization and infection with antibiotic-resistant pathogens is critical. Enhanced surveillance of ESBL-producing organisms among HIV-positive individuals is also strongly recommended.